United Kingdom : Technical Assistance Report-Public Investment Management Assessment: Climate Change Module. (IMF Staff Country Reports; Country Report ;, 2022)
This Technical Report discusses the results of applying the climate-focused module of the Public Investment Management Assessment (PIMA) to the United Kingdom (UK) in October 2021. The UK has some of the most ambitious climate mitigation targets in the world, requiring a strong role for public investment. The Climate-PIMA found that the UK has a relatively well-designed system to manage climate relevant public investment, but there is room to strengthen its institutional design and improve effectiveness. The application of the PIMA is covered in a separate companion report.